Weep not, child - Ngũgĩ wa Thiongʾo, 1938- (East African Educational publishers Ltd, 2018)
"Two brothers, Njoroge and Kamau, stand on a garbage heap and look into their futures: Njoroge is to attend school, while Kamau will train to be a carpenter. But this is Kenya, and the times are against them: in the forests, the Mau Mau is waging war against the white government, and the two brothers and their family need to decide where their loyalties lie. For the practical Kamau, the choice is simple, but for Njoroge the scholar, the dream of progress through learning is a hard one to give up.First published in 1964, Weep Not, Child is a moving novel about the effects of the infamous Mau Mau uprising on the lives of ordinary men and women, and on one family in particular"--